Menafsir Dekonstruksi Derida dalam Sosok Paus Fransiskus - Frederikus Fios (Humaniora, 2014)
Jacques Derida is a phenomenal philosopher through his philosophy of deconstruction theory. Derida showed systematically the death of structuralism. His speech shocked the world of academics in France and almost all of America and Europe. Deconstruction is a new way of reading the text, by shifting the core of a text to the side, and put the idea on the edge (the unnoticed, hidden ideas) to the center or importance. Derida rejected dichotomous, binary opposition, bipolarity, thinking model or ways of thinking that one is privileging and marginalizing other ideas. Derida thought the model that would proclaim democratic, open, and dynamic diversity that would make room for multiple interpretations of meaning or open horizon that tolerate differences in interpretation of a text. What was conceptualized by Derida is found legitimacy in practical adequacy in the figure of Pope Francis, the Catholic Church's highest leader. Francis shows a deconstructive way to lead contemporary Catholic Church. Francis has opened a new, broader, and other meaning in looking the praxis of the Church. He does not prioritize elitist lifestyle, yet puts a simple and frugal lifestyle. He changes conservative theology into progressive-liberal theology. He realized Church needs not theology but a living testimony of a good, caring, generous, compassion life that does not use religion for immoral behavior, dehumanization, and corruption. Derida did philosophical deconstruction, Francis did spiritual-leadership deconstruction. What unites both of them is a word called "deconstruction".